THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF THE STUDY OF LABOR RESOURCE FORMATION - Auezov, Omirbay Tazabaevich (SCIENCE and SOCIETY, 2026)
In this article, it is necessary to study the opinions and patterns regarding labor resources, as labor resource abundance leads to the problem of unemployment and the migration of the workforce to other regions in search of work, and it is necessary to study these processes.
Keywords: birth rate; mortality; population growth; labor resources; workforce; working age; employment; migration movement